Laporan Kasus: Pemeriksaan Luar Jenazah (Gantung Diri) - Natsir, Fanda Indiana Novita; Rizka, Rizka; Mansyur, Mauluddin; Mathius, Denny; Assegaf, S. Zulfikar (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Background: Suicide is the most common suicide method found in forensic medicine practice and is a significant cause of death, especially at productive age. Pathophysiologically, self-hanging causes mechanical asphyxia due to ligature pressure on the neck, which inhibits air and blood circulation. An external examination of the body (PLJ) plays an important role in assessing the cause and manner of death, especially if an autopsy is not performed. Case Description: A 36-year-old man was found dead in a hanging position with a blue rope and a dead knot on the right side of his neck. Examination of the outside of the body showed the presence of a circular snare measuring 31 × 0.5 cm, petekie on the eyelids and extremities, cyanosis on the nails and lips, bitten tongue, and discharge of fluid from the genitals. Stiffness of the corpse and bruises of the corpse indicate an estimated time of death in 24–36 hours. No signs of violence or other defensive injuries were found leading to the killing. Conclusions: The findings of the external examination show a typical picture of suicidal hanging. A thorough forensic examination of the body can provide sufficient evidence to support a medical-legal conclusion, even without an autopsy, and can be used as a basis for the preparation of a valid and accurate visum et repertum in the legal process.